Electrophysiological testing in concussion: A guide to clinical applications - Papathanasiou,ES; Cronin,T; Seemungal,B; Sandhu,J (Journal of Concussion, 2018)
The diagnosis of mild traumatic brain injury in concussion is difficult since it is often unwitnessed, the patient’s recall is unreliable and initial clinical examination is often unrevealing, correlating poorly with the extent of brain injury. At present, there are no objective biomarkers of mild traumatic brain injury in concussion. Thus, a sensitive gold standard test is required to enable the effective and safe triage of patients who present to the acute services. As well as triage, objective monitoring of patients’ recovery over time and separate from clinical features that patients may develop following the injury (e.g. depression and migraine) is also needed. In contrast to neuroimaging, which is widely used to investigate traumatic brain injury patients, electrophysiology is readily available, is cheap and there are internationally recognized standardised methodologies. Herein, we review the existing literature on electrophysiological testing in concussion and mild traumatic brain injury; specifically, electroencephalogram, polysomnography, brainstem auditory evoked potentials, electro- and videonystagmography, vestibular evoked myogenic potentials, visually evoked potentials, somatosensory evoked potentials and transcranial magnetic stimulation.